2015
DOI: 10.5121/ijcses.2015.6601
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art in Empirical Validation of Software Metrics for Fault Proneness Prediction: Systematic Review

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(233 reference statements)
0
1
0
Order By: Relevance
“…So, they obtained an understanding of the degree of accuracy necessary for testing in practical scenarios [15][16][17][18][19]. Bassey et al [20] demonstrated a strong correlation between complexity, coupling, size, and failure prediction. Rath et al, 2022[21] examined the influence of feature selection and ensemble techniques on the Software Reliability Prediction (SRP).…”
Section: Related Workmentioning
confidence: 99%
“…So, they obtained an understanding of the degree of accuracy necessary for testing in practical scenarios [15][16][17][18][19]. Bassey et al [20] demonstrated a strong correlation between complexity, coupling, size, and failure prediction. Rath et al, 2022[21] examined the influence of feature selection and ensemble techniques on the Software Reliability Prediction (SRP).…”
Section: Related Workmentioning
confidence: 99%